The Irony of Sectarian Claims: A Comparative Study of Salafiyyin and Nahdiyyin Religious Practices in the Shafi‘i Sect Tradition in Indonesia - Hendra Oktafia Saputra (PT. Student Rihlah Indonesia, 2026)
This article examines the irony of madhhab claims in the religious practices of the Salafiyyin and Nahdiyyin communities in Indonesia, both of which identify themselves with the Shāfiʿī school of law. The objective of this research is to analyze the differing ways in which Salafiyyin and Nahdiyyin understand, interpret, and express the authority of the Shāfiʿī madhhab in religious practice. This study employs a qualitative approach with a comparative-descriptive method through an analysis of classical Shāfiʿī legal literature as well as contemporary religious discourses and practices, particularly those related to collective dhikr, tahlīl, grave visitation (ziyārat al-qubūr), tabarruk, and outward symbols of Islamic identity. The findings indicate that the contested religious practices are not entirely principled in nature but are shaped by differences in interpretive methodology (manhaj al-fahm), epistemological orientation, and the construction of socio-religious identity. This study affirms that the Shāfiʿī madhhab encompasses a broad and dynamic spectrum of views. The novelty of this research lies in situating the Salafiyyin–Nahdiyyin debate within an intra-madhhab framework, with policy implications for strengthening inclusive and moderate religious approaches in managing the diversity of Islamic practices in Indonesia.